Effect of Kettlebell Lifting on Physical Condition of Future Mechanical Engineers - А. П. Конох; Є. О. Карабанов (OVS LLC, 2016)
The objective of the paper is to study the effect of exercises with kettlebell lifting elements on the physical condition of future mechanical engineers. Materials and methods. To address the tasks set, the study used the following research methods: theoretical analysis and collation of literary sources; implementation of a pilot program of physical education through kettlebell lifting in higher agricultural educational institutions; methods of mathematical statistics. Research results. The paper focuses on the relevant issue of theoretical and methodological support of the process of improving students' physical condition. The study has determined the effect of kettlebell lifting on the physical condition of the future mechanical engineers involved in maintenance and repair of agricultural equipment and machinery. Kettlebell lifting proves to provide good physical training, has a positive effect on the human body, and strengthens health in general. The research conducted gave grounds to determine that the level of the physical condition of the test group students is satisfactory on all indicators. This meets the requirements set before the future specialists. Conclusions. The study of the effectiveness of kettlebell lifting influence on the physical condition of the test group students yielded positive results. As a result, the training improves the performance of the students' respiratory and cardiovascular systems, decreases their heart rate and blood pressure, enhances economization of the body systems performance at rest and at load, boosts the reserve capacity of these systems, reduces the recovery period after load, and improves the metabolic processes, which contributes to enhancing the organism tolerance to the unfavorable factors of the profession-related activity.